A numerical simulation model for multi-scale flow in tight oil reservoirs - Wenchao FANG; Hanqiao JIANG; Junjian LI; Qing WANG; John KILLOUGH; Linkai LI; Yongcan PENG; Hanxu YANG (Petroleum Exploration and Development, 2017)
A discrete fracture model for multi-scale flow in large-scale fractured tight oil reservoirs is proposed considering the compressibility of reservoir rock and fluid, and the non-linear flow in the tight matrix. Validation of the model is performed, followed by the field application of the model. The two-point flux-approximation scheme is adopted in the model to calculate conductivity, and small grids at the fracture intersections are eliminated by the “star-delta” transformation method to improve the computational stability. The fully implicit discretization scheme is performed on the temporal domain. Automatic differentiation technique which can improve model establishment efficiency and computational accuracy is applied in the model to solve the numerical model. The model is validated with the simulation results of Eclipse and the historical production data of a long fractured horizontal well in a tight oil reservoir in Xinjiang oilfield. Simulation results of a field-scale reservoir show that the model proposed can simulate reservoirs with large-scale complex fracture systems; well productivity is positively correlated with the scale of the stimulated reservoir volume, and the difference in planar fracture density and fracture connectivity are proved to be the key factors that lead to the heterogeneous distribution of remaining oil in tight oil reservoirs. Key words: tight oil reservoir, discrete fracture model, multi-scale coupling, fracture network, volume fracturing